Uji Toleransi Beberapa Padi Lokal Kabupaten Simeulue terhadap Tingkat Cekaman Salinitas (NaCL) pada Fase Vegetatif - Fardi Fardi; Wira Hadianto; Amda Resdiar; Sumeinika Fitria Lizma (Jurnal Agrotek Lestari, 2021)
The use of saline land for rice cultivation needs to be supported by the presence of rice genotypes that are tolerant of saline land. To obtain a gene source that is tolerant of saline soils, it is necessary to select rice genotypes in the vegetative phase. This study aims to determine the tolerance of several local rice genotypes in Simeulue Regency to the level of salinity stress (NaCl) in the vegetative phase. The research design used was a 3 x 3 factorial randomized block design (RAK) with 3 replications. The first factor consisted of three levels, namely salinity level of 0 ppm/l (control), salinity level of 2500 ppm/l and 4000 ppm/l. The second factor consisted of three levels, namely the genotypes of Fakheulut aete, Sikurek and Mas rice. Parameters observed were plant height, number of tillers per clump, root length, number of roots, wet weight of roots and dry weight of rice roots.         The results showed that the level of salinity stress had a very significant effect on plant height, number of roots, root wet weight and root dry weight of plants aged 45 HST. Significantly affected the number of tillers and root length at 45 HST. No significant effect on plant height and number of tillers aged 15 and 30 HST. The local rice genotype of Simeulue Regency had a very significant effect on the height of rice plants aged 15, 30 and 45 HST, the number of tillers aged 15 HST, had a significant effect on root length and number of roots aged 45 HST, and had no significant effect on the number of tillers aged 30, 45 HST, root wet weight and root dry weight at 45 HST. There was no significant interaction between salinity stress level and genotype on plant height, number of tillers, root length, number of roots, root wet weight and root dry weight.Keywords : Salinity land, Salinity stress level, Local rice genotype, Vegetative                      Phase.